SUPPLEMENTING CONVENTIONAL SITE INVESTIGATION TECHNIQUES OF EARTHWORKS AND SUB-GRADE SOILS WITH GEOPHYSICAL INVESTIGATION IN ROAD DESIGN - Tsegaselassie, Ashenafi; Tadesse, Samuel (Zede Journal of Ethiopian Engineers and Architects, 2023)
In the construction of road projects in Ethiopia, one of the main factors giving rise to significant delays and both increases and decreases in project cost is the huge discrepancy in earthworks quantities between the design and the construction phases. This causes budgetary uncertainties and questioning of design documents. The aim of this paper is to assess the benefits of geophysical investigations in reducing the earthworks discrepancies. Records have been collected of projects at the design stage and projects under construction, particularly drawing on information along sections of deep cut. The findings from three projects are discussed in detail and geophysical investigations have been undertaken in the field along three sections of a selected project to allow reassessment of earthworks quantities. It is concluded that lack of detailed site investigation is a major reason for cost imprecision and delays in several road projects as a result of discrepancies in earthworks quantities. It is further concluded that careful planning and implementation of ground investigations supplemented with results from a geophysical investigation would yield cost effective results and reduce the uncertainties by greatly improving earthworks predictions at the design stage.